A murine experimental model of the pulmonary thrombotic effect induced by the venom of the snake Bothrops lanceolatus - Rucavado Romero, Alexandra (2024)
Envenomings by the viperid species Bothrops lanceolatus, endemic of the Caribbean Island of Martinique, are characterized by a thrombotic effect responsible for infarcts in various organs. Until now, no experimental in vivo models of this effect have been described. In this study, we developed a mouse model of thrombosis by using the intraperitoneal route of venom injection. The venom of juvenile specimens of B. lanceolatus induced the formation of abundant thrombi in the lungs, whereas the effect was much less pronounced with the venom of adult specimens. This difference in the ability of juvenile and adult venoms occurs despite both venoms having highly similar proteomic profiles. Both adult and juvenile venoms showed a weak in vitro procoagulant effect on plasma and fibrinogen, underscoring a thrombin-like (pseudo-procoagulant) activity. In vivo, the venoms did not affect the classical clotting tests (prothrombin time and activated partial thromboplastin time) but induced a partial drop in fibrinogen concentration and limited alterations in rotational thromboelastometry parameters when injected by the i.v. route. In contrast, few alterations of these parameters were observed after i.p. injection of venoms, in conditions in which thrombosis occurred, hence evidencing the lack of a consumption coagulopathy. After i.p. injection both venoms induced a pronounced thrombocytopenia. This experimental model reproduces some of the main clinical manifestations of envenoming by this species. This model can be used to identify the toxins responsible for the thrombotic effect, to study the mechanism(s) of thrombosis and to assess the preclinical efficacy of antivenoms and novel therapies.